Porous Orbital Implant Exposure: The Influence of Surgical Technique. (April 2014) - McElnea, Elizabeth M.; Ryan, Andrea; Fulcher, Tim
Abstract Objectives: To examine orbital implant exposure rates following enucleation and evisceration. Methods: A retrospective chart review of all patients who underwent an evisceration or enucleation in a single centre over a 5-year period was performed. The indication for surgery, the type and size of orbital implant used, details of the surgical technique adopted and the postoperative complications observed, in particular orbital implant exposure, were recorded. Results: Over a 5-year period 24 patients had enucleation and 14 had evisceration; 22 of these procedures were performed by an ophthalmic surgeon with a special interest in orbit and oculoplastics while the remaining 16 procedures were performed by 5 ophthalmic surgeons with other sub-specialty interests. Orbital implant exposure occurred in 8 cases. One case had been performed by the first of these surgeons described. Implant exposure occurred in 4% of cases performed by this surgeon. The remaining 7 cases had been performed by the group of surgeons with sub-specialty interests outside of orbit and oculoplastics. Implant exposure occurred in 48% of cases performed by this group. Conclusions: Orbital implant exposure remains a significant cause of morbidity in patients undergoing enucleation and evisceration. Rates of orbital implant exposure were significantly lower when surgery was performed by an orbital surgeon. Differences in surgical technique are the most likely explanation.